Entre " nonne " et " monstre " : images " du professeur femme " dans la France de la Belle Époque - Loukia Efthymiou (French Cultural Studies, 2021)
Le « professeur femme » est inventé en 1881 par la toute jeune IIIe République dans le cadre d’une entreprise de large envergure visant à la laïcisation du système scolaire français. Soucieux de ne point nuire au succès d’une oeuvre si importante pour la stabilité du régime même, les républicains s’emploient à faire intégrer cet être « hermaphrodite » tenant autant du masculin que du féminin à la norme. Ainsi est façonnée une nouvelle identité féminine aussi paradoxale que complexe dans la mesure où elle concilie deux extrêmes : celui de la nonne laïque entièrement vouée à ses élèves et, par ailleurs, celui de la savante, usurpatrice d’une profession définie au masculin, indépendante certes, mais au prix du sacrifice de sa féminité. The "professeur femme" was invented in France by the Third Republic in 1881 as part of a large-scale enterprise aimed at secularizing the French school system. Anxious not to harm the success of such an important project for the stability of the regime itself, the Republicans tried to integrate to the feminine norms this "hermaphrodite" human being, which takes as much from the female as it does from the male (Madame le Professeur): first, by taking care to give it specific training as to its scientific and moral content and, in this regard, adequate to the limited knowledge that it must transmit to the future French wives and mothers entrusted to it; then, by endowing it with the qualities of chastity, dedication and self-denial that characterize a female model, "the nun", whom it is called to replace. Thus, was shaped at the end of the 19th century a new feminine identity, as paradoxical as it was complex, since it reconciled two extremes: that of the “lay nun” and, that, complementarily opposed, of a scholar, independent certainly but at the cost of denial and sacrifice of her femininity. At the crossroads of culture and gender, this study based on legislative and administrative texts, archives and French female secondary teachers’ testimonies explores the construction of a particular sexual, gender and professional identity.